Keeping the faith : God, democracy, and the trial that riveted a nation - Wineapple, Brenda (Random House, 2024)
"In 1925, hundreds of people descended on the sleepy town of Dayton, Tennessee, where a young schoolteacher named John T. Scopes was put on trial for including a reference to evolution in his teaching. Darwin's concept that species evolved over time through natural selection was misunderstood as challenging the Bible, faith in God, and as suggesting that men were descended from monkeys. Two legendary men, Clarence Darrow for the defense, and William Jennings Bryan for the prosecution, drew massive crowds in a trial that quickly became a circus-like media sensation. Darrow argued for individual freedom including in religion and education, and Bryan argued from a fundamentalist Christian perspective that evolution undermined faith in God and the literal truth of the Bible. Acclaimed historian Brenda Wineapple brings to vivid life the entirety of this dramatic and colorful period that exposed foundation divisions in America across race, class, and religion. Bryan had run several times, unsuccessfully, for President, and his political efforts and ambitions, vividly chronicled in this book, culminated in Dayton. Darrow was a leader of the ACLU and known as a fervent defender of laborers, and his long history of legal defense in matters of individual rights also reached its apogee in this trial of the century. In his defense of Scopes and the First Amendment protection of individual liberty, Darrow said: 'No subject possesses the minds of men like religious bigotry, and hate, and these fires are being lighted today in America'"--